TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG DISMENORE DI SMA ADVENT TOMPASO - Beverlee Leevia Kawalo; Monalisa Sitompul (Sekolah Tinggi Ilmu Kesehatan Santo Borromeus, 2022)
Adolescence is a period of transition or transition from childhood to adulthood. The changes experienced are both from the physical, psychological, social, intellectual aspects and including the growth of reproductive organs. Dysmenorrhea is menstrual pain which is the most common gynecological problem that women experience, both in adult women and women in adolescence. Young women's knowledge of dysmenorrhea is essential to the health of their reproductive systems. The purpose of this study was to look at the level of knowledge of young women about dysmenorrhea at Tompaso Adventist High School. The method used quantitatively with the design of pre experimental one group pretest research – posttest. The respondents in this study numbered 100 students. The research instrument uses a dismenorrhea test to measure the level of knowledge of students about dysmenorrhea at Adventist High School Tompaso. Paired T-test results showed significant 0.000 < 0.05, meaning a significant increase in the level of knowledge of young women about dysmenorrhea at Tompaso Adventist High School. The advice in the study should be for young women to seek more appropriate information to take precautions and treatment of dysmenorrhea, and for schools to always be active in providing reproductive health education to their students, especially about dysmenorrhea as an effort to prevent or reduce the risk.